Unambiguous determination of Plasmodium vivax reticulocyte invasion by flow cytometry. Issue 1 (January 2016) - Cho, Jee-Sun; Russell, Bruce; Kosasaivee, Varakorn; Zhang, Rou; Colin, Yves; Bertrand, Olivier; Chandramohanadas, Rajesh; Chu, Cindy S.; Nosten, Francois; Renia, Laurent; Malleret, Benoit
Graphical abstract: Highlights: Flow cytometry methodology for high throughput screening of Plasmodium vivax merozoite invasion inhibitors. Increased accuracy and objectivity of a P. vivax invasion assay. Portable assay allows for the economic usage of limited biological material under field conditions. Abstract: The invasion of CD71+ reticulocytes by Plasmodium vivax is a crucial yet poorly characterised event. The application of flow cytometry to ex vivo invasion assays promises to facilitate the quantitative analysis of P. vivax reticulocyte invasion. However, current protocols suffer from a low level of sensitivity due to the absence of a particular design for P. vivax cell tropism. Importantly, merozoite invasion into contaminating red blood cells from the schizont inoculum (auto-invasion) may confound the analysis. Here we present a stable two-color flow cytometry assay for the accurate quantification of P. vivax merozoite invasion into intracellularly labelled CD71+ reticulocytes. Various enzymatic treatments, antibodies and invasion inhibitory molecules were used to successfully demonstrate the utility of this method. Fluorescent labelling of red blood cells did not affect the invasion and early intra-erythrocytic development of P. vivax . Importantly, this portable field assay allows for the economic usage of limited biological material (parasites and reticulocytes) and the intracellular labeling of the target cells reduces the need for highly purified schizont inoculums. This assay will facilitate the study of P. vivax merozoite biology and the testing of vaccine candidates against vivax malaria.